2016
DOI: 10.15576/asp.fc/2016.15.4.129
|View full text |Cite
|
Sign up to set email alerts
|

Aleje Przydrożne Gminy Dywity – Przegląd I Potrzeby Uzupełnienia Drzewostanów

Abstract: Uniwersytet Warmińsko-Mazurski w Olsztynie Streszczenie. Zadrzewienia przydrożne są ważnym i charakterystycznym elementem krajobrazu gmin województwa warmińsko-mazurskiego. Brakuje jednak dokładnych danych na temat aktualnego stanu zachowania poszczególnych alej oraz propozycji ich ochrony. W artykule przedstawiono wyniki badań terenowych dotyczących inwentaryzacji i syntetycznej charakterystyki alej występujących w gminie Dywity oraz rodzaju i liczby drzew potrzebnych do uzupełnienia poszczególnych zadrzewień… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Janczak-Pieniążek (2013) obtained similar results by studying the condition of sweet cherries alleys in a chosen part of the Opole Province. The observations by Dynowski et al (2016) in the agricultural Commune of Dywity (Varmian and Masurian Province) were similar. There, the length of the alleys under study was six times lower than the tree-lined roadside alleys found in the area of Wolin commune.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Janczak-Pieniążek (2013) obtained similar results by studying the condition of sweet cherries alleys in a chosen part of the Opole Province. The observations by Dynowski et al (2016) in the agricultural Commune of Dywity (Varmian and Masurian Province) were similar. There, the length of the alleys under study was six times lower than the tree-lined roadside alleys found in the area of Wolin commune.…”
Section: Resultsmentioning
confidence: 56%
“…Its share was insignificant, because within the five roadside alleys under study, only 23 trees of this species were identified. During their studies on roadside alleys of the Dywita Commune (Varmian & Masurian Province), Dynowski et al (2016) also designated Canadian Poplar (Populus x canadensis) poplar as the most invasive species of the 22 linear tree species.…”
Section: Resultsmentioning
confidence: 99%
“…Recent years have witnessed a growing interest in the role played by trees and tree assemblages in rational land management, planning sustainable urban infrastructure and sustainable rural development [1][2][3][4][5]. According to the Nature Conservation Act of 16 April 2004 [6], tree assemblages in open landscapes consist of individual trees and shrubs or small clusters of trees and shrubs that do not constitute forest communities.…”
Section: Introductionmentioning
confidence: 99%